Characteristics of water pH value based on effect of acid and alkaline solution for hydroponic cultivation technique / M.F. Saaid, Ahmad Ihsan Mohd Yassin and Nooritawati Md Tahir - Saaid, M.F; Mohd Yassin, Ahmad Ihsan; Md Tahir, Nooritawati (Universiti Teknologi MARA, 2019)
Hydroponics is a technique to grow the plant without using the soil. This technique ensures that the plant gets all the nutrients needed from the water solution. The roots of plant will absorb the nutrient in water solution for the plant to be able to grow normally with several environmental factors to be considered namely oxygenation, salinity, pH level, conductivity of the nutrient solution, light intensity temperature, photoperiod as well as air humidity. Among all these factors, the pH value is one of the vital factors since the pH value contributes extremely study, the pH characteristic is investigated and evaluated specifically for hydroponics-based cultivation. Initial results showed that the pH changed drastically and sustained its value upon adding acid and alkaline at the highest concentration with an average of water pH value of 3.24 (after adding alkaline) and 4.66 (after adding acid). The pH value was consistently stable after this water mixture is left for 4 minutes. Note that the pH value is recorded from the 60th seconds upon mixed. Upon several experimental conducted it was found that the pH value changed minimally and could be neutralized upon adding purified water. In addition to that, results showed that the pH sensor can be placed in any position of the water tank based on the similar values of pH throughout the experiments.